Decoloring Methyl Orange under Sunlight by a Photocatalytic Membrane Reactor Based on ZnO Nanoparticles and Polypropylene Macroporous Membrane - Bing Hu; Jin Zhou; Xiu-Min Wu (International Journal of Polymer Science)
Decoloring methyl orange (MeOr) under sunlight was conducted in a photocatalytic membrane reactor (PMR). Zinc oxide nanoparticles (ZnO NPs) were suspended in the solution or immobilized on the membrane. The membrane was modified by grafting 2-hydroxyethyl methacrylate (HEMA) to enhance the adsorption of ZnO NPs on the hydrophobic membrane surface and improve the membrane permeability. The results show that the water fluxes through the modified membranes are higher than that through the unmodified membrane. After introducing ZnO NPs to the membrane, the water fluxes still rise with the immobilization degree of ZnO NPs. For the PMR with ZnO NPs in suspension, the photocatalytic decoloration percent (PDP) was over 98.2% after 40 min under sunlight. For the PMR with ZnO NPs immobilized on the membrane, the max of PDP was 74.3% after 6 h under sunlight, and maintained at 72% after repeated uses for five times. These results demonstrate that photocatalytic membrane reactor (PMR) based on ZnO NPs and polypropylene macroporous membrane(PPMM) could be applied in decoloring dyes.